Przedstaw trójmian kwadratowy w postaci iloczynowej.
Daje naj

Cześć!
Postać iloczynowa funkcji kwadratowej
[tex]y=a(x-x_1)(x-x_2)\\\\x_1, \ x_2\rightarrow miejsca \ zerowe[/tex]
a)
[tex]y=2x^2-5x+2\\\\a=2, \ b=-5, \ c=2\\\\\Delta=(-5)^2-4\cdot2\cdot2=25-16=9\\\\\sqrt{\Delta}=\sqrt9=3\\\\x_1=\frac{-(-5)-3}{2\cdot2}=\frac{5-3}{4}=\frac{2}{4}=\frac{1}{2}\\\\x_2=\frac{-(-5)+3}{2\cdot2}=\frac{5+3}{4}=\frac{8}{4}=2\\\\\huge\boxed{y=2(x-\frac{1}{2})(x-2)}[/tex]
b)
[tex]y=-x^2-2\sqrt3x+1\\\\a=-1, \ b=-2\sqrt3, \ c=1\\\\\Delta=(-2\sqrt3)^2-4\cdot(-1)\cdot1=(-2)^2\cdot(\sqrt3)^2+4=4\cdot3+4=12+4=16\\\\\sqrt{\Delta}=\sqrt{16}=4\\\\x_1=\frac{-(-2\sqrt3)-4}{2\cdot(-1)}=\frac{2\sqrt3-4}{-2}=\frac{-2(-\sqrt3+2)}{-2}=-\sqrt3+2\\\\x_2=\frac{-(-2\sqrt3)+4}{2\cdot(-1)}=\frac{2\sqrt3+4}{-2}=\frac{-2(-\sqrt3-2)}{-2}=-\sqrt3-2\\\\y=-(x-(-\sqrt3+2))(x-(-\sqrt3-2))\\\\\huge\boxed{y=-(x+\sqrt3-2)(x+\sqrt3+2)}[/tex]